2022
DOI: 10.24875/gmm.m22000679
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection profile in cervical lesions

Abstract: Introducción: La prevalencia de los diferentes genotipos de virus del papiloma humano (VPH) varía dependiendo de la severidad de la lesión y región geográfica. Objetivo: Identificar infecciones múltiples de VPH en lesiones cervicales de bajo y alto grado en un grupo de mujeres del Bajío mexicano referidas con citología no concluyente. Métodos: Estudio piloto de mujeres referidas de unidades del primer nivel de atención de Guanajuato, México, por citología sugerente de lesión cervical. Los raspados cervicales f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This milestone approach is primarily dependent on the availability of nationwide HPV genotype data for countries, like Ethiopia. Our finding together with other previous HPV genotype reports could be used to partly evaluate the impact of vaccination and in the future the impact of the screening program in Ethiopia [62].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This milestone approach is primarily dependent on the availability of nationwide HPV genotype data for countries, like Ethiopia. Our finding together with other previous HPV genotype reports could be used to partly evaluate the impact of vaccination and in the future the impact of the screening program in Ethiopia [62].…”
Section: Discussionsupporting
confidence: 52%
“…The reason behind the low involvement of HPV18 in cancer and high-grade cervical lesions in Ethiopia requires further studies. Generally, the difference in the proportion and type of HR-HPVs among different studies in Ethiopia and other parts of the world might vary partly due to studyspecific characteristics, heterogeneity in geographical location [62], age, life style and socio-economic status of the study participants and differences in study population, and most importantly methods used for HPV detection [49,53].…”
Section: Discussionmentioning
confidence: 99%
“…Since these genotypes belong to the α-6 and α-9 species, this could suggest that phylogenetically related HR-HPV genotypes tend to cluster together, in agreement with reports by other authors. [41][42][43] Use of other contraceptive methods: coitus interruptus, intrauterine device, bilateral tubal occlusion, vasectomy, subdermal implant, or not using any. Herpes simplex virus type 2 test was performed in a StepOne Real-Time PCR system, using the SYBR select master mix.…”
Section: Discussionmentioning
confidence: 99%
“…HPV DNA detection and virus load quantification were performed using the Seegene Anyplex™ II HPV 28 system (Seegene, Seoul, Korea), based on a real-time multiplex PCR assay that allows simultaneous amplification, detection, and differentiation of target nucleic acids of 19 high-risk HPV types (16,18,26,31,33,35,35,39,45,45,51,52,53,56,58,59, 66, 68, 69, 73, 82) and 9 low-risk HPV types (6,11,40,42,43,44,54,61,70). 24 This system allowed us to confirm the HPV diagnosis and estimate viral loads by genotype in each patient.…”
Section: Hpv Genotyping and Pathological Examinationmentioning
confidence: 99%
“…HPV infection is also associated with anal, head and neck cancers, and some cancers of the vulva, penis, and anus [ 5 , 6 , 7 ]. HPV 6 and 11 are related to recurrent respiratory papillomatosis in children, as well as approximately 90% of genital warts [ 8 ]. Studies conducted in recent decades have shown that it is capable of infecting and replicating in syncytiotrophoblast cells, causing adverse events in pregnancy (miscarriage, preeclampsia and preterm birth) [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%